General lines to build a model of innovation impact assessment processes addressed to agricultural research organisations (Sustainability in Debate, 2022)
This article is focused on a conceptual model of the innovation impact assessment process, especially directed to agricultural research organisations. This research proposes an existing methodology based on a literature review. The innovative contributions of this article are I. theoretical lines for constructing a model of impact assessment as a base for a future data based management system; II. a conceptual base of innovation impact assessment process that considers a cross-cut view of sustainability, integrating the environmental, social, policy, and economic dimensions. This article intends to present a theoretical model addressed to research and innovation organisations that will contribute to fulfilling the United Nations’ sustainable development goals towards more productive and sustainable agriculture and accomplishing stakeholder challenges and demands.